A review of gassing behavior in Li4Ti5O12-based lithium ion batteries. Issue 14 (20th March 2017) - Han, Cuiping; He, Yan-Bing; Liu, Ming; Li, Baohua; Yang, Quan-Hong; Wong, Ching-Ping; Kang, Feiyu
Abstract : This review aims to provide an up-to-date and comprehensive summary of gassing behavior in Li4 Ti5 O12 -based lithium ion batteries. Details will be given specifically on the influencing factors, possible gassing mechanisms, state-of-the art remedies and the future development of Li4 Ti5 O12 -based batteries. Abstract : Lithium ion batteries (LIBs) with high power density, extended life time, and enhanced safety properties are promising energy storage devices for pure/hybrid electric vehicles and grid energy storage. Conventional graphite anodes suffer from limited rate capability and great safety concerns. Thus the development of efficient electrode materials with long cycle stability, excellent rate capability and enhanced safety is crucial for high-power LIBs. Spinel Li4 Ti5 O12 (LTO) has emerged as a competitive anode material for high-power LIBs due to its high safety, excellent high rate capability and extremely long cycling stability. However, the severe gas generation and associated swelling observed in soft-pack batteries during charge/discharge cycles and storage, which are accelerated under elevated temperatures, become a main obstacle to the large-scale application of LTO-based LIBs. Further understanding on the severe gassing behavior in LTO-based LIBs is quite necessary since it not only seriously deteriorates their power density and cycling stability, but also leads to great safety concerns. To date, there are some research reports that specifically refer to the gassing behavior of LTO electrodes. However, there is no critical review that concentrates exclusively on the gassing of LTO-based batteries. Hence, this review aims to provide an up-to-date and comprehensive summary of the gassing behavior in LTO-based LIBs. Details will be given specifically on the influencing factors, possible gassing mechanisms, and state-of-the art remedies. An insight into the future research of LTO-based battery development is given.